EFEKTIFITAS METODE SEX EDUCATION TERHADAP SIKAP REMAJA - Jinhan Nur Oktavia; Herawati Mansur; ita yuliani (Poltekkes Kemenkes Malang, 2021)
The high number of incidents of free sex that should not be necessary, abortion, transmission of sexual diseases, to the death rates of mothers and children caused by adolescent knowledge about sex education. The method used is the study of literature. Source searching is carried out systematically using electronic databases namely googlescholar, researchgate, and scienedirect. The initial theme is in accordance with the theme of the study of literature with the last 5 years publication, then the journal is filtered according to the theme. The author found 16 journals that fit the research topic. The journals used by the authors mostly use the Chi Square analysis technique. Respondent criteria used were adolescents who applied sex education. The results of the study are effective methods of providing sex education as desired. Methods of sex education targeting large groups will be more effective using lectures or seminars, while sex education targeting small groups can use individual methods, guidance and counseling as well as interviews. Sex education Giving to adolescents must be more emphasized and use the right methods, so that the attitudes of adolescents can be more positive and better.